2007
DOI: 10.18553/jmcp.2007.13.7.570
|View full text |Cite
|
Sign up to set email alerts
|

Continuity in Methylphenidate Treatment of Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: ReseaRch Int he general adult population, the prevalence of attentiondeficit/hyperactivity disorder (ADHD) is approximately 2% to 4%. [1][2][3][4] Methylphenidate (MPH) effectively ameliorates many symptoms of adult ADHD. [5][6][7][8][9] In 1l arge 6-week randomized controlled trial of adults with ADHD,7 immediate-release methylphenidate (IR-MPH) was associated with a76% response rate, compared with a1 9% response rate for placebo. In a 6-week trial with the same response criteria, 66% of subjects treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…9,14 Few studies have investigated predictive factors for long CS treatment duration in adults, but some suggest there is an association between longer treatment duration and the use of extended-release (ER) formulations of CS. 15,19,20 Olfson and colleagues 15 also found that treatment by a psychiatrist was positively related to longer CS treatment duration. Mental health treatment in an emergency department during the 6 months before initiation of MPH treatment and younger age were related to shorter duration.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…9,14 Few studies have investigated predictive factors for long CS treatment duration in adults, but some suggest there is an association between longer treatment duration and the use of extended-release (ER) formulations of CS. 15,19,20 Olfson and colleagues 15 also found that treatment by a psychiatrist was positively related to longer CS treatment duration. Mental health treatment in an emergency department during the 6 months before initiation of MPH treatment and younger age were related to shorter duration.…”
mentioning
confidence: 97%
“…9,14 Few studies have investigated predictive factors for long CS treatment duration in adults, but some suggest there is an association between longer treatment duration and the use of extended-release (ER) formulations of CS. 15,19,20 Olfson and ORIGINAL CONTRIBUTION …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This research informs us that less than one-third( 30%) of adult patients who received MPH had am edical claim for ADD or ADHD. 2 The authors' focus in this study was continuity or length of MPH therapy in adult ADD/ADHD patients, and the median duration of treatment with the index MPH medication was 68 Editorial days (95% confidence internal [CI], 65-71 days for ER-MPH versus 39 days [95% CI, 33-52 days] for IR-MPH). Although this difference of 29 days is statistically significant, the clinical and practical significance areunknown and no doubt small.…”
Section: Add or Adhd Or What Exactly?-gigo Part II And Other Lessons mentioning
confidence: 99%
“…2 Code 314.01 accounted for 46% of the patients that received ER-MPH and 39% that received IR-MPH. Code 314.00 (without mention of hyperactivity) accounted for 48% of the patients that received ER-MPH and 53% of the patients that received IR-MPH.…”
Section: Add or Adhd Or What Exactly?-gigo Part II And Other Lessons mentioning
confidence: 99%